Legislating for corporate criminal liability in Finland: 22-year long debate revisited - Anne Alvesalo-Kuusi; Liisa Lähteenmäki (Taylor & Francis, 2022)
The criminal liability of corporations has been the subject of long debates in many countries. This article scrutinizes the 22-year long genesis of corporate criminal liability legislation in Finland. We are interested in unveiling the turns of the law-making process, and in investigating the struggle between various interest groups from a socio-historical perspective. The research data consist of legislative documents such as committee memorandums and written opinions, and the method of inquiry is content analysis. Our study reveals that the core issue of the process became whether jurisprudential principles should be changed in accordance with societal change or whether they are essentially immutable. The Act of Corporate Criminal Liability took effect in 1995, but its coverage was weakened by imposing discretionary sentencing and leaving employment offences outside of its purview. The initial aim and the very justification of the law—to place liability where it belongs—was achieved only in principle. Furthermore, the final outcome of the 1995 law served to actually prevent corporate misconducts from being processed as crimes.